Clinical outcomes and characteristics of patients hospitalized for Influenza or COVID-19 in Germany. (February 2021) - Ludwig, Marion; Jacob, Josephine; Basedow, Frederike; Andersohn, Frank; Walker, Jochen
Highlights: Male sex and old age associated with poor outcome for both diseases. Overall, inhospital mortality is twofold higher for COVID-19 patients. Ventilation time is more than three times longer for COVID-19 than for Influenza. COVID-19 patients discharged after ventilation stayed in hospital twice as long. The proportion of patients with severe outcomes higher for COVID-19 than for Influenza. Abstract: Objectives: Since the beginning of the severe acute respiratory syndrome coronavirus 2 pandemic, there is a discussion about the severity of coronavirus disease-2019 (COVID-19) in comparison to infections with seasonal Influenza. The objective of this study was to compare clinical and demographic characteristics of German patients hospitalized for infection with either SARS-CoV-2 or Influenza. Methods: This study used anonymized German healthcare claims data. Patients with a confirmed COVID-19 or Influenza diagnosis, for whom a complete hospital course was available (i.e., the patient was discharged or died in hospital) were included. The data set included detailed information on patient characteristics and hospital treatment. Patients were grouped according to whether they were transferred to the intensive care unit (ICU), received mechanical ventilation (MV), or had a severe course of the disease (SD). Charlson Comorbidity Index in the eight quarters prior to hospitalization and secondary diagnoses during hospitalization were analyzed. Results: A total of 2343 hospitalized patients with COVID-19 and 6762 hospitalized patients with Influenza were included. Fifty-four percent of the patients were male patients, with men being twice as frequent in the COVID-19 severe groups. For both diseases, patients >49 years accounted for almost three-quarters of hospital cases and hypertension, diabetes mellitus, chronic kidney disease, and chronic obstructive pulmonary disease were the most common comorbidities. The proportion of cases with ICU, MV, and SD was substantially higher for patients with COVID-19 (ICU+: 21 vs. 13 %; MV+: 15 vs. 9%; and SD+: 28 vs. 16%). Overall inhospital mortality was more than two-fold higher in COVID-19 vs. Influenza (14 vs. 6%).). The length of ventilation and hospitalization, and the proportion of patients diagnosed with acute respiratory distress syndrome, systemic inflammatory response syndrome, or acute kidney injury were considerably higher in patients with COVID-19. Conclusions: COVID-19 resulted in higher inhospital mortality and worse clinical outcomes than Influenza. This was not attributable to demographic characteristics, preexisting comorbidities, or patient triage, because the German healthcare system had not reached its limits in the pandemic. Discussions suggesting that COVID-19 and seasonal Influenza have similar severity cannot be based on clinical evidence.